The Authority of the Prosecutor in Conducting Investigations into Corruption Crimes According to Law Number 16 of 2004 - Darfebryanto, Reyza; Marwenny, Elwidarifa; Fauzi, Engrina (LPPM Universitas Ekasakti, 2025)
Corruption in Indonesia remains a persistent problem, undermining the government system, economy, and threatening social stability. This study aims to analyze the authority of prosecutors in conducting investigations into corruption crimes based on Law Number 16 of 2004 concerning the Prosecutor's Office of the Republic of Indonesia. The research questions in this study include: 1) How is the authority of the prosecutor's office regulated in investigating corruption crimes under Law Number 16 of 2004; 2) What is the mechanism for investigations conducted by prosecutors; and 3) What obstacles are faced by prosecutors in conducting investigations based on this law. This research uses normative and empirical legal methods. To address these issues, an empirical juridical type of research is employed, utilizing semi-structured interviews and the statute approach. The results show that Law Number 16 of 2004 provides a strong legal foundation for prosecutors to investigate corruption crimes. The authority is further regulated under Law Number 31 of 1999 on the Eradication of Corruption Crimes, as amended by Law Number 20 of 2001. This represents a significant challenge for the prosecutor's office and other law enforcement agencies to address. The role of prosecutors is specified in Article 1 point 1 of Law Number 16 of 2004 concerning the Prosecutor's Office of the Republic of Indonesia, and their duties and functions as investigators of corruption crimes are aligned with the provisions of Article 284 paragraph (2) of the Criminal Procedure Code (KUHAP) and Article 17 of Government Regulation Number 27 of 1983. The existence of various regulations granting investigative authority to other institutions also poses obstacles, leading to overlapping jurisdictions and differing perceptions in carrying out the investigative process. These issues form significant challenges to the authority of prosecutors as investigators of corruption crimes.